Overcoming error fossilization in academic writing: strategies for Saudi EFL learners to move beyond the plateau - Hani Hamad M. Albelihi; Arif Al-Ahdal (Asian-Pacific Journal of Second and Foreign Language Education)
Abstract The current study explores error fossilization in the academic writing of Saudi English as a Foreign Language (EFL) undergraduate learners. A manual textual analysis approach, employing corpus content analysis on writing across diverse genres including argumentative, expository, narrative, and descriptive essays was conducted to discover the fossilized errors. The results showed that certain errors, such as idiomatic language usage and subject-verb agreement, appear to be fossilized, while others diminish over time. The study highlights specific instances of error fossilization, including challenges related to articles, idiomatic language, plural markers, negative markers, and prepositions. These errors are attributed to factors such as linguistic differences between Arabic and English, limited exposure to authentic language materials, and cultural influences. This study provides valuable insights into the complexities of error fossilization among Saudi EFL undergraduates. By understanding the factors contributed to these errors and their underlying causes, educators can develop tailored approaches to language instruction, ultimately enhancing English proficiency in similar contexts.